Sacubitril/valsartan effect on left ventricular remodeling: the case of a super-responder. (16th May 2019) - Monzo, Luca; Lanzillo, Chiara; Tota, Claudia; Lino, Stefano; Fusco, Armando; Minati, Monia; Martino, Annamaria; Calò, Leonardo
Abstract: Sacubitril/valsartan has been shown to improve clinical outcomes in patients with heart failure and reduced ejection fraction (HFrEF), but its effects on left ventricular (LV) systolic function and reverse remodeling parameters remain to be established. We hereby describe the case of a 41 year old man with HFrEF and severe reduction of left ventricular ejection fraction (LVEF). The patient was first treated with triple HF therapy (beta-blocker, angiotensin converting enzyme inhibitor and mineralocorticoid antagonist), but after three months he was still symptomatic and with an LVEF firmly low. In consideration of poor response to therapy, we switched angiotensin converting enzyme inhibitor to sacubitril/valsartan to the maximum tolerated dose (49/51 mg bid) with a marked improvement in LV systolic function and reduction in LV volumes at follow-up. In light of the almost normalized LVEF the patient was also removed from the list for the implantation of a cardiac resynchronization therapy defibrillator. In conclusion, our case showed a strong beneficial effect of sacubitril/valsartan on reverse remodeling and LVEF beyond the benefits of concomitant optimal medical therapy. This result is particular noteworthy because it was obtained although the patient wasn't able to reach the full dose of the drug. Physicians should always consider this drug effect when more demanding therapeutic strategies are needed for their HF patients.